From seed to profit: a comparative economic study of two Italian vertical farms - Amici, Alessandro Sebastian; Appicciutoli, Diego; Bentivoglio, Deborah; Staffolani, Giacomo; Chiaraluce, Giulia; Mogetta, Mattia; Finco, Adele (Frontiers in Sustainable Food Systems, 2025)
ObjectiveThis paper assesses the economic profitability of vertical farms producing microgreens. The study aims to estimate the financial sustainability of this class of farming systems, by classifying the most impacting costs for this sector, and if they are suitable in the Italian territory.MethodsThe study is performed by comparing key performance indicators of two vertical farms in the North of Italy. Data was obtained through semi structured interviews. Key factors considered included variable costs such as energy consumption, raw materials and labor cost, and fixed costs such as amortization and initial investment. The adopted indicators were the operational margin and the cost revenue ratio.Results and discussionFindings indicate that, under current conditions in Italy, microgreens vertical farming systems are economically profitable. From the results, it emerges that the real energy consumption is not an impacting factor as stated in literature, along with the important water efficiency of the systems and the capability to digitalize the workflow, supporting the need for technical experts to manage efficiently all procedures. The economic outcome shows a positive operational margin for both companies. The low-cost revenue ratio confirms the financial feasibility of the systems. The framework provides valuable guidance for future research and investment strategies, emphasizing the importance of fundings for agronomic strategies suited to combine profitability and sustainability.